PELATIHAN BAHASA INGGRIS KOMUNIKATIF UNTUK PEMANDU WISATA DI SAFARI TOUR AND TRAVEL TASIKMALAYA - Wida Mulyanti; Sundari Purwaningsih (Universitas Perjuangan Tasikmalaya, 2020)
This community service program takes the form of communicative English training for tour guides in Tasikmalaya. This program is organized based on requests from one of the Safari Tour and Travel tour guides who report that they have difficulty communicating in English when confronted with foreign tourists. After conducting the survey, it can be concluded that the tour guides have good knowledge of English, but are not trained in its use. Therefore, they need communicative English training. The steps used in providing training materials are: orientation, training, feedback and continuation. Pre-test and post-test are carried out at the beginning and end of the meeting and show an increase in the acquisition of test scores at the end of the meeting. From the results of these tests it can be concluded that this service contributes to improving communicative English skills for tour guides.